(3GdVYaGA hGdeJQhcjfs - (3GdfSGFj , CMeO Hf Ydj Hf TYjH Hf Ydj Hf SfGf Hf HMQ Hf OjfGQ GdfSGFj, CHh YHO GdQMef,J (B303 (3g` s
(3ChdgG (B:s
(3CNHQfG GdTjN CHh eMeO YHO GdbGOQ Hf YHO Gddg GdQgGhi jhe GdKdGKGA JGSY TgQ QeVGf ef SfI KeGf hSJeGFI bGd MOKfG CHh eMeO GdMSf Hf QTjb s
(3BNQgG (B:s
(3Ce GdCShO , jQhi YfgG CMeO Hf jhfS ZjQ KbI (B[ (3hjdi Pdc ChQGb Yf GdfSGFi CjVkG ai JSejI ef de jQh Yfg ZjQ QLd hGMO , hWHbGJ GdeMOKjf ef GUMGH fGaY ehdi YHO Gddg HQf YeQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HBNQgG SeGYGJ hbQGAGJ SfI (B646 (3g` , (B648 (3g`s
(3hGdfSNI ebGHdI Ydi fSNI CNQi HBNQgG SeGY SfI (B571 (3g` s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B171 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B244s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs